Conversion factors for effective dose and organ doses with the air kerma area product in patients undergoing percutaneous transhepatic biliary drainage and trans arterial chemoembolization. (April 2020) - Brambilla, M.; Cannillo, B.; Guzzardi, G.; D'Alessio, Andrea; Galbiati, Andrea; Matheoud, Roberta; Carriero, A.
Highlights: The conversion factors depend on the amount of copper filtration in interventional systems. An algorithm for deriving effective and organ doses from KAP has been established in biliary procedures. The algorithm provides accurate estimates of effective and organ doses in biliary procedures. The algorithm could be easily extended to other interventional procedures and incorporated in radiation dose monitoring systems. Abstract: Conversion factors used to estimate effective (E) and organ doses (HT ) from air Kerma area product (KAP) are required to estimate population doses in percutaneous transhepatic biliary drainage (PTBD) and trans arterial chemoembolization (TACE) interventional procedures. In this study, E and HT for ten critical organs/tissues, were derived in 64 PTBD and 48 TACE procedures and in 14, 540 irradiation events from dosimetric, technical and geometrical information included in the radiation dose structured report using the PCXMC Monte Carlo model, and the ICRP 103 organ weighting factors. Conversion factors of: 0.13; 0.19; 0.26 and 0.32 mSv Gy −1 cm −2 were established for irradiation events characterized by a Cu filtration of 0.0; 0.1; 0.4 and 0.9 mm, respectively. While a single coefficient of conversion is not able to provide estimates of E with enough accuracy, a high agreement is obtained between E estimated through Monte Carlo methods and E estimated through E/KAP conversion factors accounting separately for the different modes of fluoroscopy and the fluorography component of the procedures. An algorithm for the estimation of effective and organ doses from KAP has been established in biliary procedures which considers the Cu filtration in the X-ray irradiation events. A similar algorithm could be easily extended to other interventional procedures and incorporated in radiation dose monitoring systems to provide dosimetric estimates automatically with enough accuracy to assess population doses.